2006
DOI: 10.1016/j.ejcts.2006.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Is extreme obesity a risk factor for cardiac surgery?An analysis of patients with a BMI≥40

Abstract: Cardiac surgery can be performed without significant increase in perioperative and 30-day mortality in obese and extremely obese patients. Overall complication rates and LOS in patients with BMI> or =40 is increased and demands attention. We provide evidence that rates of few specific complications increase with extreme obesity. For risk stratification in the setting of an obesity epidemic, we advocate an interdisciplinary approach in obese patients undergoing elective cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
109
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 21 publications
11
109
2
6
Order By: Relevance
“…Data analysis showed a benefit in survival of euthrophic and overweight patients; similar to findings published by Brikmeyer et al [17], Gurm et al [18] and Fasol et al [30], in which a BMI superior to 30 kg/m² was not associated with increased mortality [31].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Data analysis showed a benefit in survival of euthrophic and overweight patients; similar to findings published by Brikmeyer et al [17], Gurm et al [18] and Fasol et al [30], in which a BMI superior to 30 kg/m² was not associated with increased mortality [31].…”
Section: Discussionsupporting
confidence: 76%
“…However, the relationship between BMI and its effect on postoperative CABG is controversial: some studies found no significance between high BMI and mortality [13][14][15][16]; others have shown a positive correlation between obesity and postoperative complications [17][18][19]. Gurm et al [20] found a short-term protective effect of obesity in patients who had undergone CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Ogólna częstość hospitalizacji osób otyłych jest także więk-sza niż w przypadku pozostałej populacji [10][11][12]. Znany jest negatywny wpływ otyłości na śmiertelność i powikłania okołooperacyjne w chirurgii ogólnej [13][14][15][16][17][18], kardiochirurgii [19][20][21][22], urologii [23], chirurgii klatki piersiowej [24][25], ortopedii [26][27][28] i neurochirurgii [29]. Otyłość generuje więc For many years, the obesity epidemic has been observed in advanced countries, Poland included [1].…”
unclassified
“…Powikłania ze strony układu oddechowego pojawiały się w tej grupie nawet o ok. 17% częściej, niewydolność nerek -o ok. 2% częściej, infekcje rany pooperacyjnej -o 20% częściej, a rozejście się rany pooperacyjnej -o 2% [14,15,17]. W grupie pacjentów kardiochirurgicznych, u których czas pobytu na oddziale został przedłużony, przeważały osoby otyłe -było ich o 2% więcej w stosunku do pacjentów o prawidłowej masie ciała, niewydolność nerek pojawiała się o 10% częściej, a przedłużona wentylacja mechanicznao 16% [19]. Wśród pacjentów otyłych operowanych na oddziałach chirurgii klatki piersiowej powikłania ze strony ukła-du oddechowego występowały o ok. 16% częściej niż u osób o prawidłowej masie ciała [25].…”
unclassified
See 1 more Smart Citation